PD-1 inhibitor-associated type 1 diabetes: A case report and systematic review - Lin, Cuiping; Li, Xuan; Qiu, Yu; Chen, Zheng; Liu, Jianping (Frontiers in Public Health, 2022)
Objective: This study aimed to summarize the clinical characteristics of programmed death receptor 1 (PD-1) inhibitor-associated type 1 diabetes so as to improve the ability of clinicians to correctly diagnose and treat it. Methods: We reported a case of a 70-year-old woman with gastric cancer who developed hyperosmolar hyperglycemic coma during camrelizumab (a PD-1 inhibitor) treatment and was diagnosed with PD-1 inhibitor-associated type 1 diabetes. We conducted a systematic review of 74 case reports of type 1 diabetes associated with PD-1 inhibitor therapy published before June 2022. Results: The patient developed type 1 diabetes with hyperosmolar hyperglycemic coma after receiving camrelizumab chemotherapy for 6 months (9 cycles). We searched 69 English articles comprising 75 patients, all of whom had been treated with a PD-1 inhibitor (nivolumab or pembrolizumab) and progressed to diabetes after an average of 6.11 (1-28) cycles. Nivolumab combined with ipilimumab (a cytotoxic T lymphocyte-associated protein 4 inhibitor) had the shortest onset (4.47 cycles on average). A total of 76% (57/75) of patients developed diabetic ketoacidosis (DKA) at onset, and 50.67% (38/75) of patients had C-peptide <0.1 ng/mL. Most of the patients were tested for insulin autoantibodies, with a positive rate of 33.33% (23/69); of these, 86.96% (20/23) were tested for glutamate decarboxylase antibody and 46.67% (35/75) were tested for human leukocyte antigen (HLA). HLA-DR4 was the most common type. Conclusions: The progression of type 1 diabetes induced by PD-1 inhibitors is relatively rapid. Islet failure often occurs when detected, seriously endangering patients' lives. Patients treated with PD-1 inhibitors should closely monitor their plasma glucose level during treatment to detect, diagnose, and treat diabetes on time.